2018
DOI: 10.31234/osf.io/rm298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why is the Duration of Imagined Walking Underproduced? A dual-representation view on the mental imagery of locomotion

Abstract: Generally, imagining an action and physically executing it are thought to be controlled by common motor representations. However, imagined walking to a previewed target tends to be terminated more quickly than real walking to the same target, raising a question as to what representations underlie the two modes of walking. To address this question, the present study put forward a hypothesis that both explicit and implicit representations of gait are involved in imagined walking, and further proposed that the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 78 publications
(148 reference statements)
0
1
0
Order By: Relevance
“…In this method, the participants walk in place, including swinging their arms in a manner consistent with their pace of walking. It has been shown that such arm swings are effective in having participants experience a naturalistic sense of locomotion without actually moving in real space (Kunz, Creem-Regehr, & Thompson, 2009;Yamamoto, Mach, Philbeck, & Van Pelt, 2018). This locomotion method uses the physical movement of the controller(s), held by the participant, to determine forward speed in the VE.…”
Section: Locomotion Methodsmentioning
confidence: 99%
“…In this method, the participants walk in place, including swinging their arms in a manner consistent with their pace of walking. It has been shown that such arm swings are effective in having participants experience a naturalistic sense of locomotion without actually moving in real space (Kunz, Creem-Regehr, & Thompson, 2009;Yamamoto, Mach, Philbeck, & Van Pelt, 2018). This locomotion method uses the physical movement of the controller(s), held by the participant, to determine forward speed in the VE.…”
Section: Locomotion Methodsmentioning
confidence: 99%